Munkahelyteremtés és agroenergetika-vizsgálatok az Észak-Alföldön - Antal, József; Grasselli, Gábor; Szabados, Krisztián (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Both the European both the Hungarian agribusiness faced new challenges when the ris-ing world price of the crude oil brought the bio-energy products, produced on arable lands into focus. This new branch of agriculture should be paid significant attention because it is not only appropriate for the utilization of the unfavourable areas (extreme water manage-ment, shallow topsoil level) but with good technology it could generate significant labour demand which is the most important question in rural development. During the examina-tion of spreading of SRF it is necessary to examine the appropriate structural requirements (economic aspects, logistics, time and spatial dimensions) for the sake of satisfying the above mentioned complex functions and avoiding to create SRFs only because of fashion, or because of the utilization of subsidies. The aim of the author is to analyse the manage-ment aspects of SRF systems in the research, focusing on rural employment possibilities.